Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1039/c9ob00831d
|View full text |Cite
|
Sign up to set email alerts
|

Identification of crucial bottlenecks in engineered polyketide biosynthesis

Abstract: Quo vadis combinatorial biosynthesis: STOP signs through substrate scope limitations lower the yields in engineered polyketide biosynthesis using cis-AT polyketide synthases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…32 In that light, the increase as well as the decrease in turnover rates was expected, provided that it is the substrate specificity of the acceptor KS that limits the rate of a chimeric PKS. 26,41 In addition, we systematically varied the protein-protein interactions within the chimeric KSmutated PKSs; i.e., the protein:protein interface emerging from the upstream ACP docking to the downstream KS for translocation and the structure of the substrate presented to the downstream KS for uptake and processing. Overall, our approach yielded a large body of data giving insight into mechanistic details of PKS-mediated product synthesis outlined in the following on three examples:…”
Section: Resultsmentioning
confidence: 99%
“…32 In that light, the increase as well as the decrease in turnover rates was expected, provided that it is the substrate specificity of the acceptor KS that limits the rate of a chimeric PKS. 26,41 In addition, we systematically varied the protein-protein interactions within the chimeric KSmutated PKSs; i.e., the protein:protein interface emerging from the upstream ACP docking to the downstream KS for translocation and the structure of the substrate presented to the downstream KS for uptake and processing. Overall, our approach yielded a large body of data giving insight into mechanistic details of PKS-mediated product synthesis outlined in the following on three examples:…”
Section: Resultsmentioning
confidence: 99%
“…4,11 The inactivation of processing enzymes within a synthase usually results in large decreases in polyketide production and shunt products indicative of a stall in the assembly line. 12 The gatekeeping activities of KSs could explain these phenomena (Figure 1). Studies of processing enzyme knockouts in the monensin PKS showed KR knockouts are among the most severely affected.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Studies of processing enzyme knockouts in the monensin PKS showed KR knockouts are among the most severely affected. 12 This could be due to a general exclusion of the β-keto group by KSs that accept more reduced intermediates. The products of ER knockouts contain a new double bond rather than a new hydroxy group, as might be expected from the DH-mediated equilibrium between βhydroxy and α/β-unsaturated intermediates.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations